Personality traits and their impact on the social entrepreneurial intentions of management students: A test of big five personality approach - Dhruba Lal Pandey; Surendra Kumar Uprety; Nischal Risal (Journal of Innovation and Entrepreneurship, 2023)
The focus of this study is to analyze the impact of big five personality traits (proxied by agreeableness, conscientiousness, extraversion, emotional stability, and openness and social support) on social entrepreneurship intention of the students of Tribhuvan University, with the objective to examine the effect of these five personality traits and social support on social entrepreneurship intention as also the moderating effect of gender. Most of the studies focused on the impact of personality traits on social entrepreneurial intention, but ignored the situational factors proxied here by the social support. There are contradictory and contractionary findings while examining impact of big five personality traits on SEI. Most of the studies (Nga & Shamuganathan in Journal of Business Ethics, 95(2), 259-282, 2010; Yusuf & Kamil in Global Journal of Research in Social Sciences, 2(1), 65-73, 2015; Hsu & Wang in Innovations in Education and Teaching International, 56(3), 385-395, 2018; Bernardino et al. in International Journal of Gender and Entrepreneurship, 10(1), 61-82, 2018; and Seyoum et al. in Journal of Small Business and Enterprise Development, 28(3), 337-359, 2021). Similarly, studies on these issues are almost ignored in Nepalese academics and therefore the researchers attempted to assess the impact of big five personality traits on SEI which is new in the Nepalese context. The sample size was determined using Cochran's (John Wiley & Sons Incorporated, 1977) formula. The data were collected based on five-point Likert scale questionnaire administered personally and online on 385 samples and were analyzed using SMART PLS software. Structure equation modeling was used to examine the impact of the big five personality traits and social support on social entrepreneurship intention and bootstrap multi-group analysis to check the moderating effect of gender. Cronbach Alpha and composite reliability (CR) were used to check reliability, variance inflation factor (VIF) to check multicollinearity, K-S and Shapiro-Wilk test to check the normality of the data, and Fornell and Larcker criterion and HTMT ratio to check the discriminant validity. The study found that all the proxies of big five personality traits and social support positively and significantly impact on social entrepreneurship intention, but gender does not moderate the relationship. The big five personality traits remain one of the major determinants in creating entrepreneurial intention among students. The reason why, university can adopt programs to educate big five personality traits in order to develop entrepreneurial intention among graduate level students. Similarly, social support helps generate entrepreneurial intentions. The study findings confirm the effect of social support in creating entrepreneurial intention and create the scope to use TPB theory in creating entrepreneurial intention. As well, it helps university to develop programs and courses for the creating entrepreneurial intention among graduate level students.
Keywords: 650; Nepal; Social entrepreneurship; Social support; Tribhuvan University